2022
DOI: 10.3389/fpsyg.2022.918289
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating and Buffering Effect of Creativity on the Relationship Between Sense of Place and Academic Achievement in Geography

Abstract: PurposeThis study explored the relationship between sense of place and academic achievement in geography and used a mediation model to verify the mediating role of creativity in this relationship.MethodsA total of 1,037 upper secondary school students were surveyed using the Sense of Place Scale, the Innovative Behavior Scale, and their geography test scores. SPSS (version 26.0) was used for descriptive statistical analysis and correlation analysis. The PROCESS plug-in (version 4.0) was used to test the mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 168 publications
0
1
0
Order By: Relevance
“…Our research demonstrates that sense of place is positively associated with creativity, which aligns with previous research [55,110]. A neuroscience study found that sense of place is associated with individual behaviors, perceptions, and emotions [111], and a positive environment has been shown to enhance creativity [112].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our research demonstrates that sense of place is positively associated with creativity, which aligns with previous research [55,110]. A neuroscience study found that sense of place is associated with individual behaviors, perceptions, and emotions [111], and a positive environment has been shown to enhance creativity [112].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the measurement of sense of place has exhibited diverse characteristics [55]. Some researchers have developed quantitative measurement approaches for sense of place, such as the Locational Identity Scale [56] and scales assessing the seven methods of perceiving place [57], to quantify the intensity of sense of place.…”
Section: Sense Of Place and Creativitymentioning
confidence: 99%
“… Derrien and Stokowski (2014) found that sense of place can improve quality of life. In addition, it can promote pro-environmental behavior, creativity, and academic achievement in geography ( Halpenny, 2010 ; Zhang et al, 2022 ). Moreover, citizens’ worldview and consumerism were also related to sense of place ( Ontong, 2018 ; Rieh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%